2018
DOI: 10.2478/scjme-2018-0021
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and Sensitivity Analysis General Non-Conservative Asymmetric Mechanical Systems

Abstract: In this paper the concept of generalized form of proportional damping is proposed. Classical modal analysis of non-conservative continua is extended to multi DOF linear dynamic systems with asymmetric matrices. Mode orthogonality relationships have been generalized to non-conservative systems. Several discretization methods of continua are presented. Finally, an expression for derivatives of eigenvalues and eigenvectors of non-conservative system is presented. Examples are provided to illustrate the proposed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…k , It can be shown that this procedure works in principle, however, it has several drawbacks: (i) it requires specially normalized eigenvectors and reordering of equations according to Equation ( 6 , ≙ a complete system of equations (8) has to be set up and solved; (iii) since the system transfer matrix U results from a multiplication of several element transfer matrices, the product rule will produce multiple product terms in the derivatives U ω , and U k , where identical matrix products are used several times. Thus, the procedure is computationally inefficient and not recommendable for complex models of technically relevant systems.…”
Section: Direct Differentiation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…k , It can be shown that this procedure works in principle, however, it has several drawbacks: (i) it requires specially normalized eigenvectors and reordering of equations according to Equation ( 6 , ≙ a complete system of equations (8) has to be set up and solved; (iii) since the system transfer matrix U results from a multiplication of several element transfer matrices, the product rule will produce multiple product terms in the derivatives U ω , and U k , where identical matrix products are used several times. Thus, the procedure is computationally inefficient and not recommendable for complex models of technically relevant systems.…”
Section: Direct Differentiation Methodsmentioning
confidence: 99%
“…Also specific approaches are published, for example, by Fox and Kapoor 6 or Choi and Kim 7 for the generalized eigenproblem boldKboldZ=ω2boldMboldZ resulting from the ansatz boldzfalse(tfalse)=boldZ.25emcos.25emωt for undamped mechanical systems described by equations of motion boldMtruez̈+boldKboldz=bold0. Further, damped mechanical vibration systems have been studied, for example, by Zmindak 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensitivity analysis is a methodology used to validate the stability of implemented MADM methods.it is also used to validate many mechanical applications in both static and dynamic analysis [30] this is the most important predominant factor to be determine, for applying these techniques practically. The main reason that lead to this analysis is the Variations in weighing criteria which effect the attribute rankings.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…The behaviour of mechanisms under loading was checked by the finite element method using linear elasticity theory. The numerical simulation was realized on high precision positioning system [6][7][8], the model of which is given in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%